Asymmetric price transmission of Indonesian coffee - Kamaruddin; Masbar; Sofyan Syahnur; Shabri A. Majid (Cogent Economics & Finance, 2021)
Almost all previous studies of Asymmetric Price Transmission (APT) only focused on speed perspective. The study aims to investigate the effect of coffee prices in the global market on the Indonesian producer market in magnitude, speed, and direction perspectives. This study used the data of coffee prices at the producer level, coffee prices at the world market, and Indonesian GDP for the period 1980 to 2018. To examine the behavior of the APT, we use the NARDL model. The results show that there is a nonlinear co-integration of coffee prices between the global market and the Indonesian producer market. The APT occurs both in the long run and short run. The existence of the APT is not only in speed but also in magnitude and direction sides. The response of coffee prices in the producer market is higher and faster when the world coffee prices decrease. It indicates the failure to perform a perfectly competitive market structure in Indonesia. If the performance of the national economy is stable, Indonesian coffee producers are more likely to increase global coffee prices. However, in the Indonesian economic recession, coffee producers tend to suffer welfare loss due to the negative shock of world coffee prices. Therefore, policymakers should not only focus on economic growth but also has to make some policies assessing perfect competition in domestic agricultural markets.
Keywords: C54; E32; 330; asymmetric transmission; producer welfare; Shin's NARDL; world-producer coffee prices